Dehydrogenative Coupling of a Tertiary Silane Using Wilkinson's Catalyst. Issue 18 (9th June 2016) - Azpeitia, Susan; Fernández, Belén; Garralda, María A.; Huertos, Miguel A.
Abstract : Wilkinson's catalyst [Rh(PPh3 )3 Cl] results active in the dehydrogenative coupling of the tertiary silane SiMeH( o ‐C6 H4 SMe)2 (L1 ) to give ( o ‐C6 H4 SMe)2 MeSi–SiMe( o ‐C6 H4 SMe)2 (L2 ). The stoichiometric reaction of [Rh(PPh3 )3 Cl] withL1 affords a new silyl‐hydrido‐Rh III complex [Rh(H){SiMe( o ‐C6 H4 SMe)2 }Cl(PPh3 )] (1 ), which results also active in the dehydrocoupling ofL1 . The unsaturated Rh III compound [Rh(H){SiMe( o ‐C6 H4 SMe)2 }(PPh3 )][BAr F 4 ] (2 ) was synthesized by reaction of1 with NaBAr F 4 and shows lower catalytic activity in this process. Compound2 reacts with a second equivalent ofL1 to form [Rh{SiMe( o ‐C6 H4 SMe)2 }2 ][BAr F 4 ] (3 ), which is inactive in catalysis. Our results allow proposing1 as an active species in the catalytic reaction and suggesting the formation of3 as a deactivation process when the unsaturated compound2 is used as catalyst. Abstract : Wilkinson's catalyst results active in the dehydrogenative coupling of the tertiary silane SiMeH( o ‐C6 H4 SMe)2 to give ( o ‐C6 H4 SMe)2 MeSi–SiMe( o ‐C6 H4 SMe)2 . The stoichiometric reaction of [Rh(PPh3 )3 Cl] with the substrate affords a silyl‐hydrido‐Rh III complex, which is an active specie in the catalytic process.